BREACH OF BETROTHAL IN MALAYSIA: A COMPARATIVE STUDY BETWEEN SYARIAH AND CIVIL LAW - Nurulmahfuzah binti Masmi Tajuddin; Gunardi, Setiyawan (Universitas Islam Indonesia, 2024)
It has become customary nowadays for the engagement event to be celebrated with an official ceremony that consumes large expenses accompanied by the giving of valuable and luxurious gifts. The question arises whether the expenses that may be incurred or any losses that may arise during the period before the engagement is called off can be claimed as well as whether the engagement gift may be returned due to humiliation and embarrassment that the party must bear in consequence of the cancellation of engagement. This study aims to explain the concept of breach of betrothal from Syariah and a legal perspective. The paper will analyse the issue from a Syariah point of view and at the same time evaluate the statute in Malaysia between Syariah and civil law related to the matter as well as supported by the case law. A qualitative methodology was employed to analyse the data including books, articles, websites, and the internet. This study conducted interviews with a lawyer and 2 academics. Results findings show that the Islamic Family Law Act or Enactment only applies to Muslims in the Syariah court while non-Muslims are dealt with under the Contract Act 1950 in Civil court relating to betrothal in Malaysia. This study recommends the resolution of the issue of breach of betrothal in Malaysia to create a harmonious Malaysian society as well as to reduce the cases of breaking a promise to marry in the society.